The Raw and the Cooked / Introduction to a Science of Mythology: I - Levi-Strauss Claude (Penguin Books, 1990)
A seminar work of structural anthropology that cuts wide and deep into the mind of man. Illustrations, Table of Symbols, Overture, Theme and Variations, Bororo Song, Ge Variations, The ''Good Manners'' Sonata, A Short Symphony, Fugue of the Five Senses, The Opossum's Cantata, Well-Tempered Astronomy, Three-Part Inventions, Double Inverted Canon, Toccata and Fugue, Chromatic Piece, Rustic Symphony in Three Movements, Divertissement on a Folk Theme, Bird Chorus, The Wedding, Bibliography, Index of Myths, General Index.